2020
DOI: 10.33182/bc.v10i1.976
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health and Wellbeing of EU Citizens in the UK: A Systematic Review of the Qualitative Literature

Abstract: Moving to a new country impacts on migrants’ mental health and wellbeing. There are over 3.6 million European Union citizens living in the United Kingdom. We conducted a systematic review of the qualitative literature to explore what is known about their mental health and wellbeing at the post-migration stage in pre-Brexit period. We searched five databases from 1st January 2009 to 19th February 2019; Web of Science, MEDLINE, CINAHL, SocIndex and Scopus for studies. Ten papers reporting nine studies were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…We identified four core question concepts, relating to the population (Central and/or Eastern European; Migration), location (United Kingdom) and ‘intervention’ (General Practice). Relevant search terms were identified from Medical Subject Heading codes and peer‐reviewed publications 46,47 . Nine medical bibliographic databases were searched (Applied Social Sciences Index Abstracts; Cumulative Index to Nursing and Allied Health Literature; Embase; International Bibliography of the Social Sciences; OvidMEDLINE; PsycInfo; Scopus; Sociological abstracts; and Web of Science).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified four core question concepts, relating to the population (Central and/or Eastern European; Migration), location (United Kingdom) and ‘intervention’ (General Practice). Relevant search terms were identified from Medical Subject Heading codes and peer‐reviewed publications 46,47 . Nine medical bibliographic databases were searched (Applied Social Sciences Index Abstracts; Cumulative Index to Nursing and Allied Health Literature; Embase; International Bibliography of the Social Sciences; OvidMEDLINE; PsycInfo; Scopus; Sociological abstracts; and Web of Science).…”
Section: Methodsmentioning
confidence: 99%
“…Relevant search terms were identified from Medical Subject Heading codes and peer‐reviewed publications. 46 , 47 Nine medical bibliographic databases were searched (Applied Social Sciences Index Abstracts; Cumulative Index to Nursing and Allied Health Literature; Embase; International Bibliography of the Social Sciences; OvidMEDLINE; PsycInfo; Scopus; Sociological abstracts; and Web of Science). Single‐item searches were combined through Boolean operators to develop concept‐wide searches.…”
Section: Methodsmentioning
confidence: 99%
“…Further, immigrants' economic concerns transcend those at their personal level only; they also impair their ability to send money to family members who stayed behind and to use other instruments of remittance (Carling, 2014). Overall, then, the coronavirus places immigrants at a dual disadvantage: its direct effect on their own economic wellbeing "looming job loss, income loss, workload decline" (Witteveen and Velthorst, 2020: 27222) and its indirect impact on their families abroad ("transnationality")-possibly heightening their psychological stress as well (Teodorowski, Woods and Kennedy, 2020).…”
Section: Economic Wellbeingmentioning
confidence: 99%
“…One of the core principles of the EU, the free movement of persons, allows EU citizens to move freely and reside in other member states without any visa requirements and to exercise the same rights (e.g., employment and benefits) as citizens of the host country. A recent systematic review (Teodorowski et al, 2020) reported found that prior to Brexit, many EU citizens experienced difficulties, including poor employment conditions or pay (e.g., Christensen & Manthorpe, 2016), social isolation (e.g., O'Brien & Tribe, 2014) and language barriers (e.g., Farr et al, 2018). As the referendum approached, many also directly experienced or were aware of increasing anti‐migrant rhetoric and abuse towards EU citizens, particularly Eastern Europeans (Rzepnikowska, 2019).…”
Section: Introductionmentioning
confidence: 99%